The Role of Trade Costs in Global Production Networks : Evidence from China’s Processing Trade Regime - Ma, Alyson C.; Van Assche, Ari (2012)
In a seminal contribution, Yi (2003) has shown that vertically specialized trade should be more sensitive to changes in trade costs than regular trade. Yet empirical evidence of this remains remarkably scant. This paper uses data from China's processing trade regime to analyze the role of trade costs on trade within global production networks (GPNs). Under this regime, firms are granted duty exemptions on imported inputs as long as they are used solely for export purposes. As a result, the data provide information on trade between three sequential nodes of a global supply chain: the location of input production, the location of processing (in China) and the location of further consumption. This makes it possible to examine the role of both trade costs related to the import of inputs (upstream trade costs) and trade costs related to the export of final goods (downstream trade costs) on intra-GPN trade. The authors show that intra-GPN trade differs from regular trade in that it not only depends on downstream trade costs, but also on upstream trade costs and the interaction of both. Moreover, intra-GPN trade is more sensitive to oil price movements and business cycle movements than regular trade. Finally, the paper analyzes three channels through which intra-GPN trade have amplified the trade collapse during the recent Global Recession.